The careful physicist’s guide to modified gravity in the UV - Coltman, Ben (2021)
In this thesis we investigate scalar and scalar-tensor field theories and their relation to low energy modifications of Einstein’s General Relativity (GR), as well as their mathematical validity and self-consistency. We begin by outlining the cosmological constant problem, and how large quantum corrections lead to unnatural space-time curvatures. Going into depth, we present a rearrangement of GR which emphasises the global structure within the Einstein equations. Preceding in this manner, we examine global modifications of GR which semi-classically act to insulate the highly Ultra-Violet (UV) sensitive loop corrections to the vacuum energy from the curvature of space-time. We explore the consequences of a manifestly local variant of this model, studying the UV sensitivity to place bounds on resulting cosmological profiles, the effect of phase transitions on fine-tuning, and its compatibility with inflation.